The legal regulation of the international couples property relationships in the EU - Greco, Ubaldo (2020)
When the couple has an international dimension due to some foreign element, either because of the different nationality or residence of its members or because of the location in various States of the goods that compose its patrimony, etc., it is highly desirable to lay down harmonized rules for achieving uniform solutions to any problems that might arise. In doing so, legal safeguard is enhanced and the freedom of movement of the international couples is extremely favored. In order to achieve those objectives, the Council Regulations (EU) 2016/1103 and 2016/1104 were promulgated, whose full implementation has taken place early 2019 and, even though they were conceived within the European Union, are aimed at spouses and domestic partnerships from anywhere in the world in their subjective aspects.